A Patient With AIRE Mutation Who Presented With Severe Diarrhea and Lung Abscess. Issue 1 (January 2021) - Soyak Aytekin, Elif; Serin, Oguzhan; Cagdas, Deniz; Tan, Cagman; Aksu, Tekin; Unsal, Yagmur; Yeni, Selma; Orhan, Diclehan; Ozon, Zeynep Alev; Tezcan, Ilhan
Abstract : Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) (polyglandular endocrinopathy type 1) is a rare autosomal recessive disorder caused by mutations in the autoimmune regulator gene (AIRE). The major clinical features of APECED are hypoparathyroidism, adrenal insufficiency (Addison disease), and chronic mucocutaneous candidiasis. This disease is also associated with multiple other and uncommon autoimmune (autoimmune hepatitis, autoimmune enteropathy, atrophic gastritis with or without pernicious anemia, gonadal failure, diabetes mellitus, hypothyroidism, functional hyposplenism), ectodermal (alopecia and vitiligo), and inflammatory (intestinal lung disease, nephritis) features. Here, we report a case of a 13-year-old Turkish boy who presented wih enteropathy and lung abscess. Molecular genetic analysis demonstrated a homozygous frameshift mutation (p.Asp70fs, c.208_209insCAGG) in exon 2, in AIRE gene. APECED may present with severe, life-threatening infections due to functional hyposplenism. Multidisciplinary approach, careful follow-up, and molecular genetic studies are needed.